Anesthetic management of a patient with 15q tetrasomy for dental treatment - Hase,Yuri (2018)
Abstract Background and objectives 15q tetrasomy is a chromosomal abnormality that is a part of the heterogeneous group of extra structurally abnormal chromosomes. This syndrome is characterized by epilepsy, central hypotonia, developmental delay and intellectual disability, and autistic behavior. This is the first report of the anesthetic management of a patient with this syndrome. Case report We administered general anesthesia for dental treatment in a patient with 15q tetrasomy. Conclusions Appropriate planning for the prevention of complications such as seizures and hypotonia, and for delayed emergence from anesthesia, is required. Specifically, choosing short-acting drugs that do not induce seizures, together with suitable monitoring, resulted in successful anesthetic management of the patient with 15q tetrasomy.